Blunted Heart Rate Response as a Potential Endophenotype of Substance Use Disorders: Evidence from High-Risk Youth - Evans, Brittany E.; Greaves-Lord, Kirstin; Euser, Anja S.; Koning, Tess; Tulen, Joke H. M.; Franken, Ingmar H. A.; Huizink, Anja C. (Frontiers in Pediatrics, 2015)
Background: Children of parents with a substance use disorder (CPSUD) are at increased risk for developing problematic substance use later in life. Endophenotypes may help to clarify the mechanism behind this increased risk. However, substance use and externalizing symptoms may confound the relation between dysregulated physiological stress responding and familial risk for substance use disorders. Methods: We examined whether heart rate (HR) responses differed between CPSUDs and controls. Participants (aged 11-20 years) were CPSUDs (N=75) and controls (N=363), semi-matched on the basis of sex, socioeconomic status and ethnicity. HR was measured continuously during a psychosocial stress procedure. Substance use and externalizing symptoms were self-reported and mother-reported, respectively. Results: A piecewise, mixed effects model was fit for HR across the stress procedure, with fixed effects for HR reactivity and HR recovery. CPSUDs showed a blunted HR recovery. CPSUDs reported drinking more frequently, were more likely to use tobacco daily, were more likely to report ever use of cannabis and used cannabis more frequently, and exhibited more externalizing symptoms. These variables did not confound the relation between familial risk for substance use disorders and a blunted HR recovery. Conclusion: Our findings suggest dysregulated autonomic nervous system responding in CPSUDs and contribute to the accumulating evidence for autonomic nervous system dysregulation as a potential endophenotype for substance use disorders.